Peran Budaya Tradisional Bali Dalam Mendukung Presidensi G20 di Bali Indonesia - Ni Luh Anita; I Ketut Merta; Ida Ayu Sasmitha Putri (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
The purpose of this study is to determine the influence that traditional culture in Bali has on the performance of the G20 Presidency. This research method uses quantitative methods. The sample in this study was 90 art actors in Denpasar City consisting of music, dance, and performing arts. Data analysis techniques use validity tests, reliability, correlation tests, simple regression tests, coefficient of determination tests, and ANOVA model tests. The results showed that traditional culture has a correlation with the G20 presidency in a high category. Traditional culture has a significant effect on the G20 presidency. The results of the coefficient of determination (adjusted R) test were obtained by 0.395 which was concentrated at 39.5% This shows that the influence of Traditional Culture on the G20 Presidency is 39.5%. While the remaining 60.5% was influenced by other variables that were not studied in this study